Introducing Vulnerability Theory for Nursing Research Concerning Infants in Out of Home Care - Gregory-Wilson, Rachel (Nursing philosophy, 2025)
Nurses often play crucial roles on teams involved in providing care to infants and families in the context of child protection services, making them well-placed to research topics concerning these groups. Developed by North American legal scholar Martha Fineman in 2008, a contemporary macro-legal-political theory with potential to inform studies related to the nexus between healthcare and law is ‘vulnerability theory.’ Conceiving vulnerability as a universal, inevitable, and enduring aspect of the human condition, it contends that the onus is on the State to respond to universal vulnerability by ensuring institutions and structures do not confer unfair advantage or disadvantage. When access to rights is particularly difficult, a ‘targeted group approach’ should be considered as well as consideration of the notion that responses to vulnerability have the potential to increase vulnerability. This paper outlines the background of vulnerability theory, explaining its key tenets and criticisms, before considering how it might be useful to inform studies focused on infants in out of home care.